DIGITALIZATION OF LEADERSHIP COMMUNICATION, WORK MOTIVATION, AND NURSE PERFORMANCE: A LITERATURE REVIEW - Dewa Gede Wisnu Wardana; Ni Luh Putu Inca Buntari Agustin; I Gusti Ngurah Made Kusuma Negara; Yustina ni putu Yusniawati (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Background: Digitalization is a process of transformation from a traditional era to a digital era influenced by technological developments. Digitization affects various aspects of life, including the health sector, especially leadership communication which influences work motivation and nurse performance which is visible during the Covid-19 pandemic. The purpose of this literature review is to identify digitalization in leadership communication, work motivation, and performance of nurses or employees. Design: This research design is a literature review. Data Sources: Search for articles using four journal databases, namely OWL (Online Wiley Library), Google Scholar, Pubmed, and Science Direct. Review Methods: Used PRISMA Flow Diagram to find a total of 11 articles that met the inclusion criteria were reviewed. Results and conclusion: The results of the review of the article entitled